Study on Nutritional and Therapeutic Properties of Pleurotus ostreatus - Vemuri, Praveen Kumar (Asian Journal of Pharmaceutics (AJP), 2022)
Background: Pleurotus ostreatus, the oyster mushroom, is primarily an edible mushroom with high nutritional value and biomedical relevance, as it contains numerous bioactive components that generate the development of therapeutic effects. Aim: The purpose of this study is to determine the phytopharmacological effects of P. ostreatus. Material and Methods: To depict the medicinal properties of oyster mushroom, FTIR, HPLC, GC-MS, anticancer and antimicrobial activities were conducted. Results: The presence of 12 bioactive compounds was revealed using gas chromatography-mass spectrometry, and components in the extract were identified and quantified using high pressure liquid chromatography. The extract’s anticancer efficacy against HeLa and MCF-7 at 25 μg/ ml and exhibits strong cytotoxicity activity of 6.8 μg/mL and 17.5 μg/mL, respectively. Antimicrobial efficacy of P. ostreatus aqueous extract against Bacillus megaterium and Bacillus amyloliquefaciens seems promising. A significant inhibitory zone was discovered against B. megaterium at 90 μg/ml of sample. Conclusion: Our primary data from this research work can help in the detection of bioactive component’s, the determination of their efficacy through in vivo research, and the demonstration of their safety and efficacy in clinical trials.